Strengthening the Assertiveness of Minangkabau Female Students Through Group Guidance Based on Sumbang Duo Baleh Values for Preventing Sexual Harassment in Higher Education - Desi Herlina; Yarmis Syukur (AL-ISHLAH: Jurnal Pendidikan, 2025)
Sexual harassment remains a pervasive issue in higher education, often exacerbated by a lack of assertive behavior among female students. In the context of Minangkabau culture, Sumbang Duo Baleh—a set of traditional values governing ethics and decorum—can serve as a foundation for character-based interventions. This study aimed to examine the effectiveness of group guidance based on Sumbang Duo Baleh in strengthening assertiveness among Minangkabau female students to prevent sexual harassment. A quasi-experimental design with a pretest-posttest control group was employed. Twenty Minangkabau female students were randomly assigned to an experimental group (receiving Sumbang Duo Baleh-based guidance) and a control group (receiving standard group guidance). Assertiveness levels were measured using a Likert-scale questionnaire. Data were analyzed using the Wilcoxon Signed-Rank Test and Mann-Whitney U Test. The experimental group showed a significant increase in assertiveness scores from pretest to posttest (Z = -2.805, p 0.005), moving from low to high categories. In contrast, the control group showed only a moderate increase. Between-group analysis also showed significant differences in posttest scores (p = 0.011), indicating the higher effectiveness of the Sumbang Duo Baleh-based intervention. Integrating local wisdom into group guidance effectively enhances assertive behavior, empowering students to respond to potential harassment. This culturally grounded approach not only preserves traditional values but also strengthens character education within higher education institutions.